2021
DOI: 10.1021/acs.nanolett.1c03448
|View full text |Cite
|
Sign up to set email alerts
|

Twin Boundary Superstructures Assembled by Periodic Segregation of Solute Atoms

Abstract: Twinning is a common deformation mechanism in metals, and twin boundary (TB) segregation of impurities/solutes plays an important role in the performances of alloys such as thermostability, mobility, and even strengthening. The occurrence of such segregation phenomena is generally believed as a one-layer coverage of solutes alternately distributed at extension/compression sites, in an orderly, continuous manner. However, in the Mnfree and Mn-containing Mg−Nd model systems, we reported unexpected three-and five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Notable advances in scanning transmission electron microscopy (STEM) at atomic resolution have made a key contribution to unveiling many unexpected structures and composition distributions at GBs. Recent discoveries of GB structural transformation in Cu, 9 periodic arrays of solute atoms and the formation of superstructures at GBs in Cu, 1,24 Mg, 6,[25][26][27] Ni, 7,19,28 MgO, 5 and Al 2 O 3 , 4,17 and space-charge-driven interface segregation in oxides 8,29,30 are noteworthy examples demonstrating the critical role of atomic-level direct probing.…”
Section: Introductionmentioning
confidence: 99%
“…Notable advances in scanning transmission electron microscopy (STEM) at atomic resolution have made a key contribution to unveiling many unexpected structures and composition distributions at GBs. Recent discoveries of GB structural transformation in Cu, 9 periodic arrays of solute atoms and the formation of superstructures at GBs in Cu, 1,24 Mg, 6,[25][26][27] Ni, 7,19,28 MgO, 5 and Al 2 O 3 , 4,17 and space-charge-driven interface segregation in oxides 8,29,30 are noteworthy examples demonstrating the critical role of atomic-level direct probing.…”
Section: Introductionmentioning
confidence: 99%
“…Such a deposition mode enables the synthesis of nanotwin crystal structures (Figure S2). Previous studies have shown that heteroatoms can segregate at grain boundaries after annealing treatment, resulting in a local concentration surge of ∼4 orders of magnitude. Given the nearly zero solubility of Re in Cu, Re can be easily separated from Cu, facilitating its segregation at TBs upon high-temperature annealing following the Brunauer–Emmett–Teller (BET) theory; meanwhile, the adsorption of Re dopants can significantly reduce the corresponding grain boundary energy . After pulsed electrodeposition, the sample was subsequently annealed at 400 °C to obtain the Re-doped Cu TB (Re/TB-Cu-400).…”
Section: Resultsmentioning
confidence: 99%